Future Directions in Sea Otter Research and Management - Davis, Randall W.; Bodkin, James L.; Coletti, Heather A.; Monson, Daniel H.; Larson, Shawn E.; Carswell, Lilian P.; Nichol, Linda M. (Frontiers in Marine Science, 2019)
The conservation and management of sea otters has benefited from a dedicated research effort over the past 60 years enabling this species to recover from a few thousand in the early 20th century to about 150,000 today. Continued research to allow full, pre-exploitation recovery and restoration of nearshore ecosystems should focus on at least seven key challenges: (1) Defining sea otter populations at smaller spatial scales that reflect this species’ life history and dispersal patterns; (2) Understanding factors that regulate sea otter population density with a focus on index sites that are representative of the variety of littoral habitats occupied by sea otters around the North Pacific Rim; (3) Quantifying the effects of sea otters on the littoral community with a focus on how food availability limits population and ecosystem recovery and on predicting the effect of sea otter reoccupation on commercially valuable invertebrates; (4) Making sea otter monitoring programs comparable across geo-political boundaries through international collaboration to optimize survey efforts both spatially and temporally and to determine the cause of changes in sea otter demographics; (5) Evaluating the conservation benefits of sea otter reintroductions into historical habitat; (6) Assessing the socioeconomic costs and benefits of sea otter range expansion to anticipate and mitigate conflicts; (7) Recognizing in conservation and management plans that sea otters can be significantly affected by higher level predators in some circumstances. Many of these challenges will require new tools including the next generation geolocation tag technology that will allow assessments of long-range movements, dispersal and gene flow in various populations.